CHURU-KOHO POTTERY OF LAM DONG PROVINCE IN RELATION TO CHAM POTTERY - Van Mon Truong (Tạp chí Khoa học Đại học Đà Lạt, 2023)
This article examines Churu-Koho pottery in relation to Cham pottery in Central Vietnam and the Central Highlands. Research shows that Churu-Koho pottery (Lam Dong Province) is related to Cham pottery in Bau Truc (Ninh Thuan Province) and Binh Duc (Binh Thuan Province) and to the pottery of the Sa Huynh culture (Quang Ngai Province), which dates back to 3,000 BP. They are similar in name, visual arts, type, and pottery firing method. These types of pottery have been common in Central Vietnam and the Central Highlands for a long time. However, they have moderately fallen in number, especially Churu-Koho pottery. Therefore, preserving and promoting this heritage in economic, cultural, social, and tourism development is critical. We use the research methods of ethnology and anthropology, including fieldwork, participant observation, interviews, and comparison, combined with the theories of historical particularism of Franz Boas, cultural ecology of Julian Steward, and cultural acculturation of American anthropologists to analyze and explain the similarities and differences among the types of pottery.